The story of the amulet - Nesbit, Edith (Lahore Readings, 2021)
At the end of Five Children and It the five children promised not to ask the Psammead for another wish as long as they lived, but expressed a half wish to see it again some time. They find 'it' again in a pet shop in Camden Town, and their magic adventures start over again. 'It' leads them to a magic amulet - half of it actually - which they use it to try and find the other half. It takes them back to ancient Egypt and Babylon. The Queen of Babylon visits them in London, bringing all her ancient customs with her - which is awkward. They visit the lost continent of Atlantis. They see Julius Caesar in the flesh, but none of these adventures run smoothly, and if they forget the 'word of power' or lose the amulet, what would happen to them?
Keywords: Fiction